The Relationship Between Hepcidin-Mediated Iron Dysmetabolism and COVID-19 Severity: A Meta-Analysis - Peng, Denggao; Gao, Yanzhang; Zhang, Li; Liu, Zhichao; Wang, Huan; Liu, Yingxia (Frontiers in Public Health, 2022)
Backgrounds: Hepcidin has been identified as a systemic iron-regulatory hormone. Recent studies have suggested that iron metabolism disorders may be involved in the pathogenesis of acute respiratory distress syndrome and multiple organ dysfunction in coronavirus disease 2019 (COVID-19). Objectives: To re-evaluate the hepcidin-related iron metabolism parameters and explore the relationship between hepcidin-mediated iron dysmetabolism and COVID-19 severity. Methods: COVID-19 is classified as mild and moderate as non-severe, severe and critical as severe. A meta-analysis was conducted. Four bibliographic databases were comprehensively searched up to December 31st 2021. Results: Six unique studies with data from 477 COVID-19 patients were included. Compared to non-severe cases, severe cases had higher hepcidin (standardized mean difference (SMD), -0.39; 95% Confidence Interval (CI) [-0.76,-0.03]; P=0.03) and ferritin (SMD, -0.84; 95% CI [-1.30, -0.38]; P=0.0004). In five out of six studies, a total of 427 patients were tested for serum iron, and there were significant differences in their levels between severe and non-severe cases (SMD, 0.22; 95% CI [0.02,0.41]; P=0.03). A total of 320 patients from four out of six studies were tested for transferrin saturation, and the statistical difference was not significant (SMD, 0.06; 95% CI [-0.17,0.28]; P=0.64). Further studies are needed to verify whether targeting the hepcidin-mediated iron metabolism axis may influence the outcome and treatment of COVID-19. Conclusion: Targeting the iron metabolism axis, with hepcidin antibody preferred, may be a more promising treatment for severe COVID-19, but further clinical and experimental validation is required.